1997
DOI: 10.1042/bj3210021
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal multifunctional enzyme of β-oxidation metabolizing d-3-hydroxyacyl-CoA esters in rat liver: molecular cloning, expression and characterization

Abstract: In the present study we have cloned and characterized a novel rat peroxisomal multifunctional enzyme (MFE) named perMFE-II. The purified 2-enoyl-CoA hydratase 2 with an M(r) of 31500 from rat liver [Malila, Siivari, Mäkelä, Jalonen, Latipää, Kunau and Hiltunen (1993) J. Biol. Chem. 268, 21578-21585] was subjected to tryptic fragmentation and the resulting peptides were isolated and sequenced. Surprisingly, the full-length cDNA, amplified by PCR, had an open reading frame of 2205 bp encoding a polypeptide with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 44 publications
(32 reference statements)
3
56
1
Order By: Relevance
“…MFE1 hydrates 2E-enoyl-CoA to 3S-hydroxyacyl-CoA and subsequently dehydrogenates the 3S-hydroxyacyl-CoA to 3-ketoacyl-CoAs, which is a naturally occurring pathway in the ␤-oxidation of straight chain fatty acids (9,10). MFE2, the other peroxisomal multifunctional enzyme, which also possesses 2E-enoyl-CoA hydratase and 3-hydroxyacyl-CoA dehydrogenase activities, converts the 2E-enoyl-CoA into the corresponding 3-ketoacyl-CoA via a 3R-hydroxyacyl-CoA intermediate (11)(12)(13)(14)(15). MFE2 has a broad substrate spectrum, and is able to hydrate the enoyl-CoA esters of straight chain fatty acids, 2-methyl-branched fatty acids, and bile acid intermediates, and it can dehydrogenate the straight chain and branched chain 3-hydroxyacyl-CoAs (14, 16 -19).…”
mentioning
confidence: 99%
“…MFE1 hydrates 2E-enoyl-CoA to 3S-hydroxyacyl-CoA and subsequently dehydrogenates the 3S-hydroxyacyl-CoA to 3-ketoacyl-CoAs, which is a naturally occurring pathway in the ␤-oxidation of straight chain fatty acids (9,10). MFE2, the other peroxisomal multifunctional enzyme, which also possesses 2E-enoyl-CoA hydratase and 3-hydroxyacyl-CoA dehydrogenase activities, converts the 2E-enoyl-CoA into the corresponding 3-ketoacyl-CoA via a 3R-hydroxyacyl-CoA intermediate (11)(12)(13)(14)(15). MFE2 has a broad substrate spectrum, and is able to hydrate the enoyl-CoA esters of straight chain fatty acids, 2-methyl-branched fatty acids, and bile acid intermediates, and it can dehydrogenate the straight chain and branched chain 3-hydroxyacyl-CoAs (14, 16 -19).…”
mentioning
confidence: 99%
“…In contrast, another group (Qin et al 1997) found that CA had no effect on 17 -HSD IV protein levels in liver. Although we could detect constitutive expression of the mRNA and/or protein in many other tissues including testes, heart, and adrenals in the absence of exposure, expression of 17 -HSD IV could not be induced by PPC in these tissues even after long-term exposure to relatively high doses of PPC.…”
Section: Discussionmentioning
confidence: 91%
“…WY or DBP only weakly induce the full-length protein and the fragments. (3) Fragments of similar sizes with activities associated with 17 -HSD IV have been isolated by other groups (Adamski et al 1992, Qin et al 1997. Isolation and characterization of a 32 kDa protein with 2-enoyl-CoA hydratase 2 activity from rat liver led to the cloning of the full-length rat 17 -HSD IV (Qin et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Human contains only two ACOX enzymes catalyzing straight-chain and branched-chain acyl-CoA dehydrogenation, respectively [58,59]. The second and third steps in peroxisomal β-oxidation are catalyzed by multifunctional enzymes MFP1 or MFP2 (L-or D-bifunctional proteins) [60][61][62]. The final step in peroxisomal β-oxidation involves a thiolytic cleavage of the acyl-CoA catalyzed by either 3-ketoacyl-CoA thiolases a or b, or SCPx [63][64][65], resulting in the release of a chain-shortened acyl-CoA and acetyl-CoA or propionyl-CoA, depending on the substrate initially oxidized.…”
Section: An Overview Of Peroxisomal β-Oxidationmentioning
confidence: 99%